Association Between Hepatitis B Infection and Pancreatic Cancer: A Population-Based Analysis in the United States. Issue 7 (August 2018) - Desai, Rupak; Patel, Upenkumar; Sharma, Shobhit; Singh, Sandeep; Doshi, Shreyans; Shaheen, Sana; Shamim, Sofia; Korlapati, Lakshmi Shirisha; Balan, Shuba; Bray, Christopher; Williams, Renee; Shah, Nihar
Abstract : Objectives: The aim of this study was to assess the role of hepatitis B (HepB) infection in the causation of pancreatic cancer and the predictors of pancreatic cancer and mortality. Methods: We identified pancreatic cancer patients 11 to 70 years of age from the 2013–2014 National Inpatient Sample. Pearson χ 2 test and Student's t -test were used for categorical and continuous variables, respectively. We assessed the association of HepB and pancreatic cancer and the independent mortality predictors by multivariate analyses. Results: Of 69, 210 pancreatic cancer patients, 175 patients with a history of HepB and 69, 035 patients without a history of HepB were identified. Compared with the pancreatic cancer–non-HepB group, the pancreatic cancer–HepB group consisted more of younger (mean, 60.4 [standard deviation, 7.4] years vs 68.2 [standard deviation, 12.1] years), male, black, and Asian patients with low household income and nonelective admissions. The odds of developing pancreatic cancer among the HepB patients were significantly higher (adjusted odds ratio, 1.24; 95% confidence interval, 1.056–1.449; P = 0.008). Black race, age ≥ 65 years, and male sex demonstrated greater odds of mortality. Conclusions: This study concluded up to a 24% increased likelihood of pancreatic cancer among the HepB patients. Blacks showed greater odds of pancreatic cancer and related mortality.